Black butler. 13 - Toboso, Yana, 1984- (Yen, 2013)
"His betrothed's unexpected skill with a sword having narrowly saved him from a gory fate at the gnashing jaws of the undead, Earl Ciel Phantomhive, along with his intrepid butler, Sebastian, fights to see another day aboard the doomed Campania. But as they draw nearer to the heart of the Aurora Society's scheme to reanimate the dead, the pair are met by the beautiful young 'Kaiser,' who holds all the keys to this mystery in the palm of his gloved hand, platinum blond locks fluttering in his wake" -- from publisher's web site.